Characteristics of the new AtriCure cryoFORM® cryoablation probe for the surgical treatment of cardiac arrhythmias. (3rd April 2017) - Schroeter, Thomas; Misfeld, Martin
ABSTRACT: Introduction : Atrial fibrillation has a significant impact on patient mortality and morbidity. In particular, stroke is a frequent complication associated with atrial fibrillation. In recent years, various treatment options have been developed that are based on the elimination of atypical electrically active atrial areas. Areas covered : This manuscript presents a new cryoablation probe from AtriCure Inc. In addition to describing the characteristics of the probe, we also discuss atrial fibrillation and its surgical therapy options as well as the basics of cryosurgery. The cryoFORM® cryoablation probe is an ablation system developed for cardiothoracic surgeons that utilizes nitrous oxide (N2 O) to create continuous transmural lesions that block propagation of atrial activation. The main features of the probe are an excellent working capacity due to the use of N2 O, high flexibility, and, in combination with the cryoICE® Box V6, an active defrost mode for quick detachment. Expert commentary : The cryoFORM® ablation probe is a new device for the treatment of atrial fibrillation using N2 O as an energy source. The probe is made from stainless steel and has a corrugated surface, a design that provides a higher flexibility than the cryoICE probe.